Participation of Islamic Groups in the Development of Science through Digital Publications (Case Study in Central Lampung Regency) - One Untoro; Hartoyo; Hertanto (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2026)
Digital transformation has reshaped the landscape of scientific knowledge production, distribution, and legitimation. In the context of Indonesian Muslim society, Islamic groups are increasingly engaged in digital spaces; however, such engagement does not necessarily translate into substantive participation in scientific development. This article analyzes the patterns of participation of Islamic groups in scientific development through digital publications in Central Lampung Regency using a qualitative case study approach with thematic analysis. The empirical basis of this study relies on in-depth interviews with 25 key informants, representing 5 members from each organization, and a comprehensive analysis of digital artifacts, including official websites, social media accounts (Facebook, Instagram, WhatsApp groups), YouTube channels, and electronic journals managed by the groups. The study maps the participation of Muhammadiyah, Nahdlatul Ulama (NU), Salafi, LDII, and Jama’ah Tabligh based on three main indicators: development of digital resources, online forum activities, and digital science publications. By integrating Saskia Sassen’s perspective on digital space as a global social infrastructure, Manuel Castells’ concept of the network society, and Beth Simone Noveck’s notion of collaborative knowledge-based participation, the article demonstrates that digital participation among Islamic groups occurs in hierarchical and non-linear forms. The main findings reveal disparities in digital participation that are not solely driven by technological access but are primarily influenced by differences in organizational orientation toward knowledge, institutional capacity, and the ability to manage sustained digital interaction. This article seeks to offer an interpretive schema for understanding the digital participation of local Islamic groups in scientific development, thereby providing a localized perspective on the sociology of religion and science.